Building on Experience : Improving Social Protection in Uruguay and the Plan for Social Equity - Reuben, William; Miodosky, Marisa; Watanabe, Eri (World Bank, Washington, DC, 2012)
The note highlights the need to establish an accurate monitoring and evolution (M&E) system for the Plan de Equidad (PE) that combines monitoring and evaluation with social accountability and citizens' participation mechanisms. Fortunately, MIDES (Uruguay's Ministry of Social Development) is firmly moving in this direction. The efforts undertaken by the numerous institutions associated with the PE to link different data sets is a key step in consolidating the M&E system. The World Bank helped to organize a seminar on the M&E system aimed at making available to MIDES regional best-practice experiences. The note also encourages including and disseminating information on social services standards and quality assurance. This is a key step, together with the information generated from the participatory monitoring, for citizens to demand accountability in an organized and effective manner. The note encourages exploring the chances of installing Citizens Information Centers throughout the country to support these efforts, by making information about citizens rights available to the public and by channeling citizens' opinions to decision makers.